Pengaruh Current Rasio, Debt to Equity Rasio, dan Return on Asset terhadap Nilai Perusahaan pada Perusahaan Sektor Properti dan Real estate yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020 – 2024 - Lintang Qolbi Aini; Vidya Amalia Rismanty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the effect of the Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Assets (ROA) on firm value (Tobin’s Q) in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2024. Using a descriptive quantitative method with purposive sampling, this study involves 6 companies and 97 data observations. Data analysis was performed using panel data regression, t-test, F-test, and coefficient of determination tests. The results show that CR has a negative and significant effect on firm value with a t-value of -3.760941 and a significance level of 0.0011. Meanwhile, DER has a positive but insignificant effect on firm value with a t-value of 0.508701 and a significance level of 0.6163. ROA also has a negative but insignificant effect with a t-value of -1.254781 and a significance level of 0.2233. Simultaneously, the F-test results show a significant effect from all three variables on firm value, with an F-value of 14.37946 (greater than the F-table value of 2.975) and a significance level of 0.000001. The Adjusted R-Square value of 78.69% indicates that the independent variables explain 78.69% of the variation in firm value, while the remaining 21.31% is explained by other factors.